Prevalência da artrite idiopática juvenil em escolares prevalência da artrite idiopática juvenil em escolares da cidade de São Paulo - Schinzel, Vania [UNIFESP] (2018)
Introduction : Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease tha t affects the joints and other organs of children and adolescents. Its prevalence varies greatly from one study to another, depending on the study population and methodology employed, including data records and active patient search. Some tools may be help ful in screening suspected cases. Objective : To determine the prevalence of JIA in school children and adolescents from the City of São Paulo, Brazil, through the use of a specific questionnaire followed by a physical examination. Method : Sampling planning was performed based on information from the 2013 School Census, establishing n sample = 10,670 students, to guarantee a sampling error of 0.1% and a 95% confidence level. We performed a mapping of all private schools in the City of São Paulo, with randomi zation of those with more than 1,000 students. We sent the questionnaire "Early Diagnosis of Chronic Arthritis 12 items (DPA 12)" to the parents of all students in the selected schools. The questionnaires were corrected and returned to the schools. All s tudents with a score of 5 or more were evaluated by medical specialists in pediatric rheumatology through anamnesis and rheumatologic physical examination. The parents of the students with JIA diagnosis were alerted about the disease. Results : All 79 selec ted schools were contacted, of which 12 agreed to participate in the project (15.2%). A total of 21,119 questionnaires were sent and 5,710 were collected (27%). Among these, 108 had a score greater than or equal to 5. The children and adolescents screened were evaluated by anamnesis and physical examination by a specialist in pediatric rheumatology. Ten children were diagnosed as having JIA. Adjustment was made for sample correction and comparison between the participating and nonparticipating students. A p revalence of 0.196% (CI 95% = 0.104% 0.371%) of JIA was observed. Conclusion : The prevalence of JIA in students from the City of São Paulo was 0.196%, that is, 196 cases / 100,000 students.